Analytical assessment for comparisons of triple-t precast concrete-timber composite floor using gamma method - Akasah, Zainal Abidin; David Yeoh, David Yeoh; Lam, Kah Leong (2012)
Concrete-timber composite floor is a construction technique combining two materials, concrete and timber, connected together using some form of interlayer shear connectors either positioned discretely or continuously along the span of the floor. The interlayer connections provide the desired composite action, where the degree of this composite action is governed by the types of connection system used in the concretetimber composite system. This analytical method. The analytical method here refers to a design procedure known as Gamma Method recommended in the Eurocode 5 Annex B for bending stiffness, (EI)eff. This quantity obtained experimentally and analytically was compared and the reliability of Gamma method was investigated. concrete-timber composite system. In this method, the specific quantity to express the structural performance of the composite system is the effective paper presents the preliminary study on the structural performance of a proposed triple-T precast concrete-timber composite floor subjected to collapse load. The structural performance derived experimentally through four-point bending collapse test was compared to the same performance established using